Drylines over the interior of subtropical southern Africa - Van Schalkwyk, Lynette (Department of Oceanography, 2025)
Drylines are surface airmass boundaries separating regions of very dry air from regions of moist air. Due to changes in airflow that occur along the interface of these boundaries, they are known to act as zones of surface convergence which can trigger convection. For this reason drylines have been studied globally. Drylines regularly form over the interior of subtropical southern Africa and have also been associated with thunderstorm development and often severe thunderstorm initiation, but their seasonal characteristics, formation mechanisms and the extent to which they influence convection, are largely unknown. By utilizing ERA5 reanalysis surface specific humidity and temperature data and an objective moisture and temperature gradient detection algorithm, a drylines dataset is compiled between 1979 and 2020 for the subtropical southern African interior plateau (SAP). Drylines occur most frequently during spring and summer and almost daily in December. In this region dryline locations are very sensitive to surface moisture variations and therefor a westward shift in peak dryline frequency occurs through summer as moisture increases from the east after the dry winter months. Drylines peak first over the eastern SAP during November, but over the central and western parts in December. During years with increased surface moisture weaker moisture gradients occur in the east during mid-summer, resulting in fewer drylines, but during years with decreased surface moisture, more drylines tend to occur. During mid-summer, dryline frequencies in the east are negatively correlated with dryline frequencies in the west so that during years with high dryline frequencies in the east, low dryline frequencies tend to occur in the west and vice versa. The dryline climatology also establishes that drylines occur most frequently over the climatologically drier western parts of the SAP (western plateau) during summer. Drylines on the western plateau are then further investigated and lightning data from 2010-2021 are used to distinguish between drylines which resulted in convective storm development (convective drylines) and those that did not (non-convective drylines). It is found that 76% of drylines which occur over the western plateau during the late afternoons, when convection is most likely in the west, are convective. Convective drylines peak during December months when 12 occur on average over the western plateau region. The formation mechanisms of convective vs. non-convective drylines are determined by constructing synoptic composites during early summer (October-December) and late summer (January-March). Low-level moisture flow composites for the two days leading up to a convective dryline show that the Limpopo River Valley and Zambezi River Valley are important moisture pathways through which moisture from the southwest Indian Ocean travel in the days leading up to a convective dryline. During early summer convective drylines tend to occur after sharp increases 7 in surface moisture ahead of the dryline, in the presence of a deep Kalahari Heat Low and an upper air trough to its west. During late summer the pressure gradients are not as intense, but the Kalahari Heat Low continues to be a key component of the synoptic circulation on convective dryline days. Compared to early summer, a higher number of days with moderate CAPE (>1000 J.kg-1 ) occur in the same location that has the highest frequency of drylines during late summer, and this results in a greater proportion of dryline-related thunderstorms in southwestern Botswana, northeastern Northern Cape and western Northwest. Dryline climatology results confirm that drylines frequently occur over the SAP and that they have a meaningful impact on thunderstorm development in the drier western interior. This drylines study is completed by an investigation of the month with the highest number of convective drylines since the convective dryline record began in 2010 and an analysis of its synoptic characteristics. During December 2021, 20 convective drylines occurred on the western plateau, 8 more than the average. Record rainfall occurred over the central interior of South Africa while the drier western interior also recorded above average rainfall. A detailed analysis is performed of a 6-day convective dryline event where thunderstorms developed along the dryline daily, before being steered towards the central interior by anomalously strong mid-level winds. It is shown that a significant positive correlation exists between dryline days on the western plateau and rainfall within the domain, but also further downstream. In this thesis, drylines are shown to be an important climatological feature of subtropical southern Africa throughout summer. Dryline locations are dependent on the seasonal influx of moisture from the southwest Indian Ocean via the Limpopo and Zambezi River valleys and are often located at the western boundary of the tropical rain band edge. Drylines frequently act as triggering mechanisms for convection and therefor also influence rainfall further downstream